Morbidity, utilization of curative care and service entry point preferences in metropolitan Centro Habana, Cuba - Armando Rodríguez; Addys Díaz; Susana Balcindes; René García; Pol De Vos; Patrick Van der Stuyft
Abstract: First-line health services with a primary health care approach are a strong trigger for adequate health-care-seeking behavior. Research on the association between prevalence of chronic diseases and acute illnesses and use of health services emphasizes the importance of socioeconomic determinants in such patterns of utilization. In a cross-sectional study of 408 families in Centro Habana, Cuba, home interviews were conducted between April and June 2010 to analyze socio-demographic determinants of acute and chronic health problems and use of formal health services. Bivariate and logistic regression models were used. 529 persons reported a chronic disease. During the previous month, 155 of the latter reported an exacerbation and 50 experienced an unrelated acute health problem. 107 persons without chronic diseases reported acute health problems. Age was the strongest determinant of chronic disease prevalence. Adult women and the elderly were more likely to report acute problems. Acute patients with underlying chronic disease used formal services more often. No socio-demographic variable was associated with services use or consultation with the family physician. While the family physician is defined as the system's entry-point, this was the case for only 54% of patients that had used formal services, thus compromising the physician's role in counseling patients and summarizing their health issues. The importance of chronic diseases highlights the need to strengthen the family physician's pivotal role. New economic policies in Cuba, stimulating self-employment and private initiative, may increase the strain on the exclusively public health care system. Still, the Cuban health system has demonstrated its ability to adapt to new challenges, and the basic premises of Cuba's health policy are expected to be preserved.